2010
DOI: 10.1111/j.1476-5381.2009.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal and peripheral analgesic effects of the CB2 cannabinoid receptor agonist AM1241 in two models of bone cancer‐induced pain

Abstract: Background and purpose:The activation of CB2 receptors induces analgesia in experimental models of chronic pain. The present experiments were designed to study whether the activation of peripheral or spinal CB2 receptors relieves thermal hyperalgesia and mechanical allodynia in two models of bone cancer pain. Experimental approach: NCTC 2472 osteosarcoma or B16-F10 melanoma cells were intratibially inoculated to C3H/He and C57BL/6 mice. Thermal hyperalgesia was assessed by the unilateral hot plate test and mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 65 publications
3
50
1
Order By: Relevance
“…Despite these differences, administration of cannabinoid agonists produces robust analgesia in all models of cancer pain via activation of both CB1 [46,50,60] and CB2 receptors [46][47][48][49][50]. Interestingly, antinociceptive effects of both intrathecal and systemic administration of the CB2 receptor selective agonist AM1241 were abolished by intrathecal administration of the CB2 receptor antagonist SR144528, indicating a spinal site of action [48], and the effects of systemic AM1241 were blocked by naloxone [48], indicating a role of endogenous opioids, which warrants further investigation. Such interactions have previously been demonstrated in keratinocytes in naive rats [61], and may indicate interplay between the endogenous nociceptive systems at multiple levels of the pain pathways.…”
Section: Cb1 Receptor Modulation Of Pain Processing In Models Of Chromentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these differences, administration of cannabinoid agonists produces robust analgesia in all models of cancer pain via activation of both CB1 [46,50,60] and CB2 receptors [46][47][48][49][50]. Interestingly, antinociceptive effects of both intrathecal and systemic administration of the CB2 receptor selective agonist AM1241 were abolished by intrathecal administration of the CB2 receptor antagonist SR144528, indicating a spinal site of action [48], and the effects of systemic AM1241 were blocked by naloxone [48], indicating a role of endogenous opioids, which warrants further investigation. Such interactions have previously been demonstrated in keratinocytes in naive rats [61], and may indicate interplay between the endogenous nociceptive systems at multiple levels of the pain pathways.…”
Section: Cb1 Receptor Modulation Of Pain Processing In Models Of Chromentioning
confidence: 99%
“…Studies in models of cancer pain have revealed differing effects on the expression of cannabinoid receptors within the CNS, with some groups reporting an upregulation of CB1 receptor in the L5 DRG in mice injected with squamous cell carcinoma into the hindpaw [46], while others studying models of bone cancer report no change in expression [48,60]. Despite these differences, administration of cannabinoid agonists produces robust analgesia in all models of cancer pain via activation of both CB1 [46,50,60] and CB2 receptors [46][47][48][49][50]. Interestingly, antinociceptive effects of both intrathecal and systemic administration of the CB2 receptor selective agonist AM1241 were abolished by intrathecal administration of the CB2 receptor antagonist SR144528, indicating a spinal site of action [48], and the effects of systemic AM1241 were blocked by naloxone [48], indicating a role of endogenous opioids, which warrants further investigation.…”
Section: Cb1 Receptor Modulation Of Pain Processing In Models Of Chromentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical allodynia in mice was assessed by applying von Frey filaments to the plantar side of the paws as reported previously (Curto-Reyes et al, 2010). Mice were placed on a wire-mesh platform, covered with transparent plastic containers.…”
mentioning
confidence: 99%
“…Thus, thermal hyperalgesia was studied 4 weeks after the inoculation of NCTC 2472 osteosarcoma cells, whereas mechanical allodynia was assessed at week 2 (Curto-Reyes et al, 2010). DD04107 was dissolved in saline (2 mg/ml) and administered subcutaneously in a volume of 10 ml/kg 4 weeks after the inoculation of NCTC 2472 osteosarcoma cells for the thermal hyperalgesia studies and 2 weeks after the inoculation of NCTC 2472 osteosarcoma cells for the mechanical allodynia studies.…”
mentioning
confidence: 99%